Penerapan Cognitif Behavior Therapy pada Klien Halusinasi dan Perilaku Kekerasan dengan Pendekatan Model Stress Adaptasi Stuart dan Model Hubungan Interpersonal Peplau Di Rs Dr Marzoeki Mahdi Bogor - Hidayat, Firman; Keliat, Budi Anna; Mustikasari, Mustikasari (Jurnal Keperawatan Jiwa, 2015)
Cognitive Behavior Therapy (CBT) was designed to improve kognitif and behaviour for people having automatic negative thinking and negative behaviour. Application of CBT will change mind status and behavior of client, therefore negative behavior will be positive behavior. The objective of the final scientific paper was obtaining result description of Application of CBT on hallucinating clients and violence behaviour by using approach model of Peplau interpersonal relation in Utari room RS Dr Marzoeki Mahdi Bogor. CBT was applied on 28 clients in Utari room on 9 September-12 November 2013. CBT was appropriate therapy and can be applied to clients with hallucination and violence behavior, in which all clients can do each session of CBT. Based on the research it is recommended that CBT can be used as a therapy standard mental health nursing specialist, that can be applied on clients with hallucination and violence behavior.